Penerapan Media Youtube “Aku Paham” Dalam Pembelajaran Teks Biografi Kelas X SMK Negeri 6 Semarang - Nisa, Erika Wahidatun; Asropah, Asropah; Septiana, Ika; Warkito, Petrus Joko (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study evaluates the use of YouTube in learning biographical texts in class X of SMK Negeri 6 Semarang, focusing on its impact on student engagement and understanding. Educational videos from YouTube, combined with the Problem Based Learning (PBL) model, enhance students' active learning and critical thinking skills. This study applies a qualitative descriptive method to evaluate the use of the YouTube video "I Understand" in Indonesian learning at SMK N 6 Semarang. The goal is to understand the impact of the video on learning outcomes and teacher and student responses. Data were collected through observation, interviews, and documentation, and analyzed in a qualitative descriptive manner. The findings of the study show that YouTube videos can increase student engagement in an interesting and interactive way in learning Indonesian. The results show that the integration of YouTube with the PBL model creates a more active and problem-based learning environment, as well as supports the development of students' critical and creative thinking skills. While this combination is effective in improving the ability to write biographical texts, challenges such as internet access and technical skills need to be addressed to maximize their benefits. Recommendations for further practice include the selection of high-quality videos and the integration of videos with interactive activities for optimal learning outcomes. Keywords: Kata Kunci : Media Youtube, Teks Biografi, Pemanfaatan